Case report: Presumed contact lens-induced intracorneal hemorrhage in a diabetic dog - Jung, Sunjun; Park, Shin Ae (Frontiers in Veterinary Science, 2022)
A 10-year-old castrated male miniature poodle dog with diabetes mellitus was presented for a week history of blepharospasm and epiphora in the right eye. The spontaneous chronic corneal epithelial defect (SCCED) was diagnosed and a bandage contact lens was applied following corneal debridement with sterile cotton-tip applicators. In 1 week, SCCED was improving uneventfully, though an annular pattern of intracorneal hemorrhage was observed. The contact lens was removed and the intracorneal hemorrhage resorbed in 4 weeks. To the author’s knowledge, this is the first report of presumed contact lens-induced intracorneal hemorrhage characterized by an annular pattern in a dog.